Applied statics in the pharmaceutical industry - Millard, Steven P.; Krause, Andreas (USA Springer, 2001)
The purpose of this book is to provide a general guide to statistical methods used in the pharmaceutical industry, and to illustrate how to use S-PLUS to implement these methods. Specifically, the goal is to: *Illustrate statistical applications in the pharmaceutical industry; *Illustrate how the statistical applications can be carried out using S-PLUS; *Illustrate why S-PLUS is a useful software package for carrying out these applications; *Discuss the results and implications of a particular application; The target audience for this book is very broad, including: *Graduate students in biostatistics; *Statisticians who are involved in the industry as research scientists, regulators, academics, and/or consultants who want to know more about how to use S-PLUS and learn about other sub-fields within the indsutry that they may not be familiar with; *Statisticians in other fields who want to know more about statistical applications in the pharmaceutical industry.
Keywords: PHARMACEUTICS